Measuring and examining innovation in Philippine business and industry - Jose Ramon G. Albert; Francis Mark A. Quimba; Ramonette B. Serafica; Gilberto M. Llanto; Jana Flor V. Vizmanos; Jose Carlos Alexis C. Bairan (Philippine Institute for Development Studies (PIDS), 2017)
Innovation involves implementing new or significantly improved goods and services, production processes, marketing, or organizational methods for adding value. The measurement of innovation provides a mechanism for benchmarking national performance, and for examining innovation and its relation to economic growth. Further, examining determinants and bottlenecks to innovation among firms provides inputs to mainstreaming of policies on innovation. This paper describes and discusses the results of the 2015 Survey of Innovation Activities, conducted by the Philippine Institute for Development Studies. Survey results suggest that less than half of the firms in the country are innovators, with larger-sized firms innovating more than micro, small, and medium establishments. Government needs to have a champion for developing stronger policies and interventions to support and encourage innovation. It is also important to improve information dissemination on public programs available to assist firms in innovating. Networking, linkages, and collaboration among the government, industry associations, and universities and research institutions also require further enhancement.
Keywords: 330; innovation; product innovation; process innovation; organizational innovation; marketing innovation; micro; small and medium enterprises (MSMEs)